Whole-food plant-based Jumpstart for a Deaf and Hard of Hearing cohort - Friedman, Susan M.; Scheuer, Kim; Beha, Beth Garver; Dewhirst, Maria; Barnett, Ted D. (Frontiers in Nutrition, 2023)
Deaf and Hard of Hearing (DHH) patients are at high risk of developing chronic illness, and when they do, are at higher risk of poor outcomes than in a hearing community. Rochester Lifestyle Medicine Institute adapted its online, Zoom-based, medically-facilitated 15-Day Whole-Food Plant-Based (WFPB) Jumpstart program, to give DHH participants knowledge, skills, and support to make dietary changes to improve their health. Adaptations included having a medical provider present who is fluent in American Sign Language (ASL), is board-certified in Lifestyle Medicine, and has a Master of Science in Deaf Education; spotlighting participants when asking a question during the Q&A session; using ASL interpreters; utilizing closed captioning/automatic transcription during all Zoom meetings; and employing a Success Specialist to provide outreach via text and email throughout the program. Participants had significant positive changes in their eating pattern. They reported improvements in biometric measures as well as in how they were feeling. They all reported that they planned to continue to eat a more WFPB diet than they did prior to Jumpstart. All either agreed or strongly agreed that they learned important information, were confident that they knew the best eating pattern for health, and gained the skills they needed to make changes. Although this was a small pilot program, it suggests that this model can be used to provide education and support for behavior change that will lead to improved health in a DHH community.